Is Movement Political? The Body as Witness (KULT_online, 2019)
Bodies of Evidence (Passagen Verlag, 2018), edited by Gurur Ertem and Sandra Noeth, offers a comprehensive corpus of observations on different localities and experiences, which portray the body as a predominant medium and as a socio-political construct. The book comprises different fields of inquiry that, through a series of essays, case studies, dialogues, artistic sketches and interviews, suggest multiple perspectives on the body – from the viewpoint of the precarious bodies themselves – “in, as and of evidence” (p. 15).